Making Research Matter Steps to Impact for Health and Care Researchers - Lamont, Tara (Policy Press, 2021)
"EPDF and EPUB available Open Access under CC-BY-NC-ND licence. Written by a leading expert in the field, this practical and accessible book is an essential guide to knowledge exchange, impact and research dissemination in health and social care. Providing the why, what, who, how and when of research impact, the book helps researchers turn raw findings into useful, high-impact evidence for policymakers, practitioners and the public. It will help researchers at all stages of their career to maximise the impact of their work."